PC3 and PC5 amplitude pulsation variation to the solar wind parameter at low latitude / Mohd Haizarul Muiz Jamaludin - Jamaludin, Mohd Haizarul Muiz (2013)
This thesis present the variation of Pc3 and Pc5 amplitude pulsation to the solar wind speed and dynamic pressure at low latitude using magnetic data collected from the Magnetic Data Acquisition System (MAGDAS) station in Langkawi island (LKW) Malaysia between 2008 and 2009. The variations are explained by selecting 10 days of maximum and minimum solar wind speed and wind pressure in the period of two years. Results show that the days with high wind speed above 600km/s has mean amplitude Pc3 0.18nT and Pc5 0.93nT. The wind speed below 300km/s produced lower Pc3 amplitude with mean 0.09nT while for the Pc5 amplitude with mean 0.3 InT. The change of the dynamic pressure also will change the Pc3 and Pc5 amplitude pulsation. According to the result, the dynamic pressure must be related to the change of Pc3 and Pc5amplitude.